Investigation Of Effects Of Cross-Sections on The Ray-Effect Distortions - Sağlam, S. (İstanbul Kültür Üniversitesi Yayınları, 2006)
In this study, a wellknown numerieal method has been used to solve neutron transport equation and the ray-effeet anomaly observed on the results of the method hase been introdueed. To examine the effeets of eross-seetions on the ray-effeet, two Benehmark problems have been ehosen as test problems. Then, two dimensional transport code, TWOTRAN-1I has been exeeuted for these problems for 84-816 approximations. Finally, by eomparing all the results with eaeh other, the effeets of eross-seetions have been examined in detail.
Keywords: ray-effect; cross-section; distortions; ray etkisi; kesit; çarpıtmalar